2020
DOI: 10.1002/ptr.6846
|View full text |Cite
|
Sign up to set email alerts
|

The effect of geniposide on chronic unpredictable mild stress‐induced depressive mice through BTK/TLR4/NF‐κB and BDNF/TrkB signaling pathways

Abstract: The purpose of this study was to estimate the pharmacological effect of geniposide (GEN) on depression, caused by chronic unpredictable mild stress (CUMS), and explore its potential mechanism. During the 6 week CUMS procedure, the mice were treated with GEN (10, 40 mg/kg) by gavage once daily for 3 weeks. As a result, the GEN treatment remarkably improved the behavioral manifestations and suppressed the generations of inflammatory cytokines both in vivo and in vitro. The MDA level was significantly increased, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Relevant studies have shown that NF-κB is pivotal for modulating the TLR4-mediated proin ammatory cascade (Chen et al, 2021;Xu et al, 2020). Moreover, the NF-κB activation is correlated with IKKdependent IκBα phosphorylation and the translocation of cytosolic NF-κB p65 to the nucleus (Qu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that NF-κB is pivotal for modulating the TLR4-mediated proin ammatory cascade (Chen et al, 2021;Xu et al, 2020). Moreover, the NF-κB activation is correlated with IKKdependent IκBα phosphorylation and the translocation of cytosolic NF-κB p65 to the nucleus (Qu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To date, six BTK inhibitors have been approved for treating hematologic malignancies: Ibrutinib, Accalabrutinib, Zanubrutinib, Tirabrutinib, Orelabutinib, and Pirtobrutinib (Figure ). In addition to B cells, BTK is also expressed in other myeloid cells and regulates their development and immune responses through multiple signaling pathways (e.g., FcγR, CXCR, and TLR pathways). Recent studies have elucidated that BTK acts as a key upstream regulator of the PLCγ2-Ca 2+ -NFAT signaling pathway, , which regulates the formation of osteoclasts from hemato­poietic monocyte precursors and ultimately leads to bone resorption and osteolytic bone damage .…”
Section: Introductionmentioning
confidence: 99%
“…For example, clinical autopsy analyses found that patients with depression have lower level of TrkB in brain, whereas patients treated with some antidepressants (e.g., fluoxetine) have higher level of TrkB 4,5 . For another, preclinical results showed that the level of TrkB in the hippocampus of depression was low, which was reversed after the treatment of antidepressants (such as iridoid glycoside compound geniposide) 6,7 . TrkB was a specific binding site for brain derived neurotrophic factor (BDNF) and BDNF was considered a potential neurobiological marker for depression 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For another, preclinical results showed that the level of TrkB in the hippocampus of depression was low, which was reversed after the treatment of antidepressants (such as iridoid glycoside compound geniposide). 6,7 TrkB was a specific binding site for brain derived neurotrophic factor (BDNF) and BDNF was considered a potential neurobiological marker for depression. 8,9 Clinical autopsy data shown that decreased levels of BDNF and increased levels of proBDNF in brain samples from depressed patients.…”
mentioning
confidence: 99%